2022
DOI: 10.53771/ijlsra.2022.3.1.0075
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sub-MIC ciprofloxacin exposure on antibiotic susceptibility and virulence factors in Pseudomonas aeruginosa ATCC 9027

Abstract: Exposure to antibiotics below their minimum inhibitory concentration (sub-MIC) is known to be a selection pressure for the development of antibiotic resistance. In this work, we aimed to provide more understanding of how antibiotic resistance and cross-resistance developed in Pseudomonas aeruginosa under sub-MIC exposure to Ciprofloxacin. Fully susceptible P. aeruginosa ATCC 9027 was serially exposed to sub-MIC level of ciprofloxacin for 14 days to generate E1 strain, then cultured in antibiotic-free environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It should be well noted that this cross-resistance development under CIP exposure was well observed in Gram-positive bacteria such as Actinobacillus pleuropneumoniae [ 51 ], S . aureus [ 52 ], Mycobacterium tuberculosis [ 53 ]; but not in Gram-negative, ones like Salmonella enterica [ 54 ]; Pseudomonas aeruginosa [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be well noted that this cross-resistance development under CIP exposure was well observed in Gram-positive bacteria such as Actinobacillus pleuropneumoniae [ 51 ], S . aureus [ 52 ], Mycobacterium tuberculosis [ 53 ]; but not in Gram-negative, ones like Salmonella enterica [ 54 ]; Pseudomonas aeruginosa [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that serial FQ exposure resulted in cross-resistance to unrelated antibiotics and the emergence of multidrug-resistant phenotypes in S. aureus. It should be well noted that this cross-resistance development under CIP exposure was well observed in Grampositive bacteria such as Actinobacillus pleuropneumoniae [51], S. aureus [52], Mycobacterium tuberculosis [53]; but not in Gram-negative, ones like Salmonella enterica [54]; Pseudomonas aeruginosa [55].…”
Section: Plos Onementioning
confidence: 98%
“…The length of 10 days was selected as, at day 10, in most exposure replications, the bacterium maintained its MIC for at least three consecutive days. The antibiotic susceptibility profile determined via an agar- diffusion assay and virulence of the strains used in this study were reported and are provided in Tables S1, S2 and S3 [11]. All bacteria strains were stored at −80 °C in Tryptic Soya broth (TSB; HiMedia) with 30 % glycerol (TSB/glycerol 7 : 3, v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work in in vitro -induced ciprofloxacin resistance has found that after 14 days of exposure to ciprofloxacin, P. aeruginosa strains developed resistance to ciprofloxacin with MIC values increased 32-fold [11]. The resistant phenotype and its altered virulence, including protease activity, biofilm formation and motility, did not revert fully after the exposed strain was cultured for 10 days in an antibiotic-free environment [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation